Peran Bank Sumut Syariah Dalam Penghimpunan dan Distribusi Zakat Kepada Mustahik (Studi Kasus Bank Sumut Syariah Kantor Cabang Pembantu Marelan Raya) - Fikri, Muhammad; Nasution, Yenni Samri Juliati (Universitas Labuhanbatu, 2024)
The background to this research arises from changes in the dynamics of sharia banking which are increasingly felt in managing zakat, especially along with technological advances and transformation in the Islamic financial sector. This phenomenon opens up new opportunities, but also raises complex challenges that require deep understanding. In this modern era, the practice of collecting and distributing zakat in Islamic banks has become increasingly important to research in order to evaluate its effectiveness in responding to the rapidly growing demands of Islamic finance. The sustainability and success of zakat practices by Islamic banks is a major concern because of its impact on financial inclusivity and community economic empowerment. In this context, this research aims to provide a deeper understanding regarding the practice of collecting and distributing zakat by sharia banks. Identifying the challenges faced by Islamic financial institutions in managing zakat is also the focus of this research, along with evaluating the impact of zakat distribution on beneficiaries. The research methods used in this study will provide a solid foundation for collecting relevant data and analyzing it carefully. By utilizing a qualitative approach, this research will explore perceptions, policies and practices in the field, providing in-depth insight into the complexity of zakat implementation in Islamic banks. It is hoped that the results of the analysis and findings from this research can make a real contribution to the development of more effective and sustainable zakat practices in Islamic financial institutions, and in turn, can enrich understanding of the dynamics of sharia banking as a whole.